Peiminine Induces G0/G1-Phase Arrest, Apoptosis, and Autophagy via the ROS/JNK Signaling Pathway in Human Osteosarcoma Cells in Vitro and in Vivo - Yu, Lei; Chen, Yuxi; Yuan, Shaohui; Cao, Yang; Bi, Zhenggang (Frontiers in Pharmacology, 2021)
Aims: Peiminine has various pharmacological effects, especially anticancer effects. In this study, we investigated the role of peiminine on osteosarcoma and explored the intrinsic mechanism. Methods: Cell viability assay, live/dead assay, cell cycle and apoptosis analysis by flow cytometry, wound healing experiment, transwell assay and xenograft mice model were used to evaluate the antitumor effect of peiminine in osteosarcoma. The effects of peiminine on autophagy were observed by transmission electron microscopy and fluorescent LC3 puncta assay. The anticancer effect of autophagy in peiminine was evaluated by cell viability assay and western blotting after application of the autophagy inhibitor chloroquine (CQ). Reactive oxygen species (ROS) which is activated by peiminine was analyzed through a confocal fluorescence microscope and fluorescence spectrophotometer. SP600125 (a JNK inhibitor) and N-acetylcysteine (NAC, a ROS scavenger) were employed to determine the contribution of ROS/JNK signaling pathway in osteosarcoma cells after treatment with peiminine by cell viability assay, flow cytometry, fluorescent LC3 puncta assay and western blot. Results: Peiminine inhibited osteosarcoma proliferation, and induced cell cycle arrest, apoptosis, autophagy, and suppressed metastasis in vitro. Meanwhile, the anticancer effect of peiminine is dependent on the intracellular excess of ROS and the activation of the JNK pathway. Consistently, in xenograft model, peiminine significantly inhibits tumor growth with less toxicity in vivo. Conclusions: Peiminine induces G0/G1 phase arrest, apoptosis and autophagy in human osteosarcoma cells in vitro and in vivo via the ROS/JNK signaling pathway. Our study may provide an experimental basis for peiminine as one of the alternative drugs for the treatment of osteosarcoma.